2022
DOI: 10.1155/2022/9984255
|View full text |Cite
|
Sign up to set email alerts
|

Negative-High Titer of Helicobacter pylori Antibody and Lipid Profiles

Abstract: Background. Helicobacter pylori (HP) is a causative factor for several gastrointestinal diseases. A HP seropositive antibody titer (i.e., ≥10 U/mL), a threshold indicating an HP infection, is known to be associated with changes in lipid metabolism. There is evidence that HP infection can be found in some individuals with HP antibody titer of between 3 and 9.9 U/mL (termed as “negative-high titer”). However, it is unknown about the relationship between HP negative-high titer and lipid metabolism. The present st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(22 reference statements)
1
0
0
Order By: Relevance
“…6 We found that protein digestion and absorption, primary bile acid biosynthesis and secondary bile acid biosynthesis, fatty acid degradation weakened and fatty acid biosynthesis, folate biosynthesis strengthened in H. pylori-infected patients. Multiple of studies reported the association between H. pylori infection and dyslipidemia, 59,60 it might even play a role on the development of nonalcoholic fatty liver disease (NAFLD), 61 the influence of H. pylori on the metabolism of fatty acid and bile acid we reported in this study provided evidences for that.…”
Section: Discussionsupporting
confidence: 58%
“…6 We found that protein digestion and absorption, primary bile acid biosynthesis and secondary bile acid biosynthesis, fatty acid degradation weakened and fatty acid biosynthesis, folate biosynthesis strengthened in H. pylori-infected patients. Multiple of studies reported the association between H. pylori infection and dyslipidemia, 59,60 it might even play a role on the development of nonalcoholic fatty liver disease (NAFLD), 61 the influence of H. pylori on the metabolism of fatty acid and bile acid we reported in this study provided evidences for that.…”
Section: Discussionsupporting
confidence: 58%